Action, objective, intersubjectivity: towards a theory of social action - Forlin, Francesco (ETHICS IN PROGRESS, 2013)
The reflection on intersubjectivity is a central question in the contemporary philosophical debate. In this field, current practical philosophy faces one of the most difficult challenges. Apparently, the research for a foundation of the intersubjective level seems to lead inevitably towards the abandonment of the logical-foundation theory on which the philosophy had been based up until Hegel. In this report, however, I would like to attempt something different. That is, I would like to explore the possibility of inserting the subject of intersubjectivity right into the heart of Hegelian thinking, with an aim to outline the foundation of a social action theory capable of exhibiting reasons stronger than those deriving from simple dialogic validation. It is possible, as Ho sle believed, that Hegel himself did not take this aspect of the profound dynamics of his thought too seriously, and that he had not prepared the notional categories to be able to think about it in depth. Nevertheless, the theoretical foundations of intersubjectivity, brought back to its Hegelian roots, is the fundamental cornerstone upon which to build the logical-rational foundations of social action